Inter-utilities power-exchange coordination a market-oriented approach. - Aguado, J.A (IEEE Transactions on power systems)
A decentralized operation of the transmission grid for scheduling inter-utilities power exchanges is proposed. This approach is well suited for market-oriented environments; it achieves a market equilibrium while the operational independence of each interconnected utility is preserved. We employ decomposition-coordination techniques in combination with an interior-point/cutting-plane method in order to reduce the number of iterations of the decomposition algorithm. The paper includes test results on IEEE-based systems